2009
DOI: 10.5194/acpd-9-14825-2009
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Seasonal variation of aliphatic amines in marine sub-micrometer particles at the Cape Verde islands

Abstract: Abstract. Monomethylamine (MA), dimethylamine (DMA) and diethylamine (DEA) were detected at non-negligible concentrations in sub-micrometer particles at the Cap Verde Atmospheric Observatory (CVAO) located on the island of São Vicente in Cape Verde during algal blooms in 2007. The concentrations of these amines in five stage impactor samples ranged from 0 to 30 pg m−3 for MA, 130 to 360 pg m−3 for DMA and 5 to 110 pg m−3 for DEA during the spring bloom in May 2007 and 2 to 520 pg m−3 for MA, 100 to 1400 pg m−3… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

10
56
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 41 publications
(66 citation statements)
references
References 31 publications
10
56
0
Order By: Relevance
“…Higher concentrations of aminium salts in marine atmospheric particles cooccur with higher concentrations of chlorophyll‐ a in coastal waters and the open ocean (Facchini et al, ; Gibb, Mantoura, Liss, & Barlow, ; Hu et al, ; Müller et al, ). Using chlorophyll‐ a as a proxy, Myriokefalitakis et al () estimated that approximately 0.8 Tg of amines are ejected into the atmosphere from the oceans every year.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Higher concentrations of aminium salts in marine atmospheric particles cooccur with higher concentrations of chlorophyll‐ a in coastal waters and the open ocean (Facchini et al, ; Gibb, Mantoura, Liss, & Barlow, ; Hu et al, ; Müller et al, ). Using chlorophyll‐ a as a proxy, Myriokefalitakis et al () estimated that approximately 0.8 Tg of amines are ejected into the atmosphere from the oceans every year.…”
Section: Introductionmentioning
confidence: 99%
“…Many studies have demonstrated that marine aminium aerosol particles are derived from secondary processes and are mainly formed by gas‐particle conversion (Facchini et al, ; Gibb, Mantoura, & Liss, ; Hu et al, ; Köllner et al, ; Müller et al, ; Myriokefalitakis et al, ; Yu et al, ); that is, they are unlikely to be produced by bubble bursting (Facchini et al, ). In contrast, some studies hypothesized that the aminium salts detected in marine particles are emitted from surface waters to the atmosphere by bubble bursting (Gorzelska & Galloway, ; Milne & Zika, ; Mopper & Zika, ).…”
Section: Introductionmentioning
confidence: 99%
“…We performed additional experiments with H2C2O4 to further elucidate the influence of phase state on the co-uptake process. H2C2O4 is a model organic acid frequently detected in ambient aerosols (Kawamura and Ikushima, 1993;Decesari et al, 15 2000;Yao et al, 2003;Yu et al, 2005;Müller et al, 2009) . Efflorescence of aqueous supermicron H2C2O4 particles occurs at 51.8%-56.7% RH, forming anhydrous solids .…”
Section: Uptake Into Oxalic Acid Particlesmentioning
confidence: 99%
“…The results also reveal the influence of the extent of neutralization and the change in phase state on the uptake behavior of both gases. DMA was chosen as the model R3N due to its atmospheric abundance (Müller et al, 2009;Rehbein et al, 2011;Hu et al, 2015;10 Youn et al, 2015) and unique characteristics, such as forming a non-crystallizing DMAS droplet even at low RH (Chan and Chan, 2013) and its higher hygroscopicity than that of (NH4)2SO4.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation